Deconstruction of iconic characters: binary opposition and différance in the visual-narrative design of Darth Vader, Naruto, and Mario - Ahmad Faisal Choiril Anam Fathoni; Ercilia Rini Octavia; Cahyono Budi Santosa (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2026)
Character design plays a crucial role in visual narrative effectiveness and emotional connection with audiences, yet existing scholarship privileges visual-narrative coherence over the role of contradiction in shaping emotional resonance. This study asks how Derridean mechanisms, binary opposition and différance, operate within iconic character design to generate interpretive depth. It employs a qualitative multiple-case design analyzing three purposively selected characters: Darth Vader, Naruto Uzumaki, and Super Mario. Selection followed three operational criteria: documented global iconicity, representation of three distinct visual traditions (Hollywood cinema, Japanese anime, and Japanese video games), and contrasting modes of iconization (tragic-antagonistic, heroic-developmental, and functional-iconic). Each case was analyzed through a four-stage deconstructive procedure—identification of the privileged binary, contradictory close reading, exposure of the moment of différance, and synthesis of layered meaning—applied to two defined units of analysis: visual units (silhouette, color, costume, facial configuration, movement, and symbolic marker) and narrative units (scene, action, transformation, and symbolic reversal). Interpretive claims were validated by returning each reading to its primary text, by cross-case pattern testing, and by author consensus. The analysis finds that resonance is generated not by design harmony but by sustained tension between visual meaning and narrative subversion, with each character organized around a distinct collapsing hierarchy: power/weakness, recognition/alienation, and complexity/simplicity. The study contributes an operational deconstructive procedure for visual-narrative research, reframes visual contradiction as a designed resource rather than a flaw, and extends deconstructive analysis across three cultural production contexts. As a textual analysis, it describes interpretive potential inscribed in the design and makes no claim about measured audience response; empirical reception testing remains a task for subsequent research.